The Effectiveness of Kahoot Media And e-LKPD In the Application of the Discovery Learning Model for Acid & Base Teaching In Improving Students' Learning Outcomes - Sihombing, Natasya Christie; Jasmidi, Jasmidi (Jurnal Beta Kimia, 2025)
This study aims to determine the effectiveness of using Kahoot media and e-LKPD based on the Discovery Learning model in improving student learning outcomes in acid-base solution material at SMA Negeri 10 Medan. The research method used is a quasi-experimental design with a Pretest-Posttest Non-Equivalent Control Group Design. The subjects of the study consisted of four classes: F1, F2, F3, and F5, with each class consisting of 35 students. Class F1 used Kahoot media, F2 used e-LKPD, F3 used a combination of both, and F5 served as the control class. The instrument used was an objective test in the form of 20 multiple-choice questions. The results showed that the average improvement in student learning outcomes was higher in the experimental classes than in the control class. The Independent z-test revealed a significant difference between the experimental and control classes. Thus, the use of Kahoot media and e-LKPD based on discovery learning has proven effective in improving student learning outcomes in acid-base material.